36 Use of implantable cardioverter defibrillators in elderly patients with heart failure. (June 2018) - Thornton, George; Qudah, Tareq; Asher, Alex; Singhal, Arvind; Sriranganathan, Danujan; Patel, Hitesh; Sriranganathan, Danujan; Eftychiou, Stavros; Perez, Carlos; Sotto, Imelda; Malik, Tooba; Lim, Wei-Yao; et al.
Abstract : Introduction: There is a lack of evidence to guide the use of implantable cardioverter defibrillators (ICD) in elderly patients with severe left ventricular (LV) dysfunction. We sought to assess whether age plays a role in our clinical decision making regarding suitability for ICD implantation and whether the Charlson Age-Comorbidity Index (CACI) could be a useful tool in this decision making process. Methods: We identified patients with severe LV impairment through our echo department. Data were collected on demographics, medical history and medications. Patients were categorised in to decades of age. We compared the age groups using an ANOVA for continuous variables and Chi square for categorical variables. We then selected only the elderly patients (80 years or older) and compared those who had been implanted with an ICD to those who had not to determine if specific clinical factors may have been considered in the decision for ICD implantation. Finally, we assessed if the CACI predicted survival in the whole cohort. Results: We identified 569 patients with severe LV impairment and a summary of the clinical features and differences across the age groups is displayed in table 1. These data show that older patients have more co-morbidity, are prescribed fewer heart failure medications and are less likely to be implanted with an ICD. Selecting only those patients who are 80 years of age or older (n=185), the comparison between those with and without an ICD is displayed in table 2. Table 2 Patients aged 80 years and older, a comparison between those with an ICD and those without. Survival of our whole cohort categorised in to those with a CACI score of 1–4, 5–8 or 9–16 is displayed in Figure 1 and shows a significant difference in survival based on CACI score. Conclusions: Older patients with severe LV impairment are less likely to be implanted with an ICD. It is unclear whether any objective assessments are used to aid this decision. Patients with a poor life expectancy are not recommended for ICD implantation. The CACI is a tool used in various disciplines to predict likely prognosis but has not been applied to heart failure. We have shown that it can identify patients with a worse life expectancy and perhaps this could be an objective tool to help us decide about ICD therapy, particularly in elderly patients.